Kajian Penerapan Asas-Asas Hukum Perjanjian Waralaba Internasional dalam Peraturan Pemerintah Nomor 42 Tahun 2007 Tentang Waralaba dan Implikasi Yuridisnya - Mochamad Najib Imanullah (Fakultas Hukum, Universitas Islam Bandung, 2010)
Every agreement must be made on the basis of principles of free contract, good faith, and consensus. In addition to apply these principles, a franchise agreement must also based on the principles of information-openness, partnership, equality rights and obligations, burden-sharing and the obligation to keep confidentiality. This articles examines the application of law principles of international franchise agreement as stipulated in the Government Regulation No. 42 of 2007 on Franchising and the Trade Ministerial Decree No.31 of 2008 on the Implementation of Franchising. Both regulations contain the provisions related to the principles of information-openness, partnership, equality rights and obligations the obligation to keep confidential information. Nevertheless, neither the Government Regulation No. 42 of 2007 nor and the Trade Ministerial Decree No.31 of 2008 deals with the rule of burden sharing principle. Consequently, a franchise agreement is null and void if it contain no provision of any franchise agreement principles.